Mini-implant assisted rapid palatal expansion: biomechanical principles, effects and effectiveness compared to RPE and SARPE. A narrative review - María Emilia Ordóñez Carrión , María Emilia Ordóñez Carrión (2026)
Maxillary transverse deficiency (MTD) occurs when the maxilla is narrow in relation to the mandible, leading to malocclusion. Patients with MTD frequently present unilateral or bilateral posterior crossbite, anterior crowding, and prominent buccal corridors when smiling. Over the years, several methods have been developed to address this condition, including Mini-Implant-Assisted Rapid Palatal Expansion (MARPE), which emerged as an alternative to surgical intervention and has undergone modifications and improvements.  MARPE utilizes 2 to 4 mini-implants placed in the palate to provide skeletal anchorage, thereby promoting a more parallel opening of the midpalatal suture (MPS) and inducing changes in both hard and soft tissues. Outcomes vary depending on biological, clinical, behavioral, and technical factors. The aim of this article is to conduct a narrative review using digital databases to explore the biomechanical principles of MARPE, its effects in children, adolescents, and adults, and to assess its effectiveness compared to Rapid Palatal Expansion (RPE) and Surgically Assisted Rapid Palatal Expansion (SARPE). It is concluded that MARPE is an effective tool for addressing maxillary transverse deficiency (MTD), with its success depending on several factors such as appliance design and the patient's skeletal maturity. MARPE achieves more stable expansion and presents fewer side effects compared to rapid palatal expansion (RPE). In contrast to (SARPE), it offers a less invasive approach for young adults, although its efficiency tends to decline with increasing age. Future studies could focus on the application of artificial intelligence to enhance MARPE treatment planning.